(untitled) (Dermatology Reports, 2022)
We report the case of a patient with chronic granulomatous disease and acne treated with isotretinoin, who developed a diffuse staphylococcal skin infection during the therapy. Chronic granulomatous disease is a rare genetic disorder characterized by an altered innate immunity with an increased risk of potentially lethal bacterial and fungal infections. Although chronic granulomatous disease is rare, acne is a common manifestation in these patients, but there are no data about the gold standard therapy.